Impact of delipidated estrous sheep serum supplementation on in vitro maturation, cryotolerance and endoplasmic reticulum stress gene expression of sheep oocytes. - Natalibeth Barrera; Pedro C Dos Santos Neto; Federico Cuadro; Diego Bosolasco; Ana P Mulet; Martina Crispo; Alejo Menchaca (PLoS ONE)
High lipid content of oocytes and embryos in domestic animals is one of the well-known factors associated with poor cryosurvival. Herein, we wanted to determine whether the use of delipidated estrous sheep serum during in vitro maturation (IVM) of ovine oocytes reduces the cytoplasmic lipid droplets content and improves embryo development and cryotolerance after vitrification. Cumulus oocytes complexes (COCs) were matured in vitro for 24 h in medium supplemented with whole or delipidated estrous sheep serum prior to vitrification. Neutral lipid present in lipid droplets of COCs, cleavage rate, embryo development rate on Day 6 and Day 8, and hatching rate on Day 8, were compared among experimental groups. Endoplasmic reticulum stress genes were evaluated in in vitro matured COCs under different lipid conditions prior to vitrification. The lipid droplets' content (mean fluorescence intensity) of oocytes cultured with IVM media supplemented with delipidated serum was lower than COCs matured with whole serum (7.6 ± 1.7 vs. 22.8 ± 5.0 arbitrary units, respectively; P< 0.05). Despite IVM treatment, oocytes subjected to vitrification showed impaired competence compared with the non-vitrified groups (P<0.05). No significant differences in embryo production were observed in non-vitrified COCs after maturation in delipidated or whole serum (33.4±4.9 vs 31.9 ±4.2). COCs matured in delipidated serum and subjected to vitrification showed increased expression of ATF4, ATF6, GRP78, and CHOP10 genes (ER stress markers). Collectively, our results demonstrate that although supplementation of IVM medium with delipidated estrous sheep serum reduces the presence of cytoplasmic lipid droplets in oocytes after maturation, oocyte cryotolerance is not improved. Notably, the expression of genes associated with the unfolded protein response (UPR) was increased in COCs, with fewer lipid droplets subjected to vitrification, suggesting that oocyte cryopreservation is associated with ER stress and activation of adaptive responses.